Consequences of the Pandemic on Mental Health of Healthcare Workers in the NHS - Arjun Vyas; Nantapong Butakhieo; Lina Vyas (Behavioral Sciences)
In recent years, the public health system of the United Kingdom, the National Healthcare System (NHS), has encountered difficulties that have been acknowledged in research studies and public policy discussions, such as resignations and staff shortages. During the COVID-19 pandemic, NHS healthcare workers were confronted with demanding circumstances, exacerbating the constraints of an already struggling system. With this, the authors of this paper aim to better understand the relationships between frustration at work, fear of infection, working hours, and the turnover intention of healthcare workers during the pandemic. This study employed a mixed-methods research approach, as a questionnaire survey was conducted along with an online self-administered interview questionnaire. Using mediation and moderated mediation analyses, it was found that the indirect effect of frustration at work through fear of infection on turnover intention was positively significant. Working hours moderated the mediation effect of fear of infection on the relationship between frustration at work and turnover intention. Surprisingly, the conditional indirect effect of frustration at work on turnover intention through fear of infection was the strongest among those with short working hours. This evidence was supplemented with qualitative results that enhance the understanding of why healthcare workers want to leave the system and the actions that can be taken on the organisational and policy fronts to address this issue.